Classifier Systems As Robot Architecture For Behavior Coordination (Journal of the College of Basic Education, 2022)
Classifier systems (CS) are used as control architectures for robots in order to decide what to do at each time. We will explain in this research why these systems are good candidates for behavior coordination. We will introduce our system called RACE for collecting objects according to their colors, a race is held between two robots one of them is controlled by our system the other is controlled by another external system, the job of our robot is to collect balls before the other robot catch them